New Oppiidae (Acari: Oribatida) from Vernon Crookes Nature Reserve, South Africa - Hugo-Coetzee, Elizabeth A. (Zootaxa, 2017)
Five new Oppiidae species are described from Vernon Crookes Nature Reserve, KwaZulu-Natal, South Africa, namely Globoppia vernoncrookensis sp. nov., Setoppia izinyosa sp. nov., Brachioppiella (Gressittoppia) martinezi sp. nov., Brachioppiella (G.) ricknuttalli sp. nov. and Kokoppia murvanidzeae sp. nov. A supplementary description is provided of Setoppia karinae Mahunka, 1974 which is recorded from South Africa for the first time. A total of 14 Oppiidae species is recorded from Vernon Crookes Nature Reserve.